Pengaruh Perputaran Modal Kerja dan Struktur Modal terhadap Profitabilitas pada PT Indofod CBP Sukses Makmur Tbk Periode 2014-2023 - Agus Suhartono; Iriana Kusuma Dewi; Nani Rusnaeni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The financial performance of a company is largely determined by its ability to manage working capital efficiently and maintain an optimal capital structure. In the case of manufacturing and consumer goods companies such as PT Indofood CBP Sukses Makmur Tbk, the balance between liquidity and financing decisions plays a crucial role in sustaining profitability and long-term growth. This study aims to determine the effect of working capital turnover and capital structure on profitability, both partially and simultaneously. The research employs a quantitative approach using secondary data obtained from the company’s annual financial statements over a ten-year period. Data analysis techniques include classical assumption testing, multiple regression analysis, autocorrelation testing, coefficient of determination analysis, and hypothesis testing. The results reveal that both working capital turnover and capital structure have a significant positive effect on profitability. This indicates that the more efficiently the company manages its working capital and the more effectively it maintains its capital structure, the higher its profitability will be. The findings highlight the importance of strategic financial management in optimizing operational efficiency and ensuring financial stability. Overall, this study contributes to understanding how internal financial decisions influence company performance and provides practical implications for improving profitability within the manufacturing sector.